Analysis of The Role Of E-Philantrophy Through Digital Platform and Social Media During The Covid-19 Pandemic In Human Resources Development Perspective - Rahmi, Nur (The International Journal of Business Review (The Jobs Review), 2021)
Abstract. The development of e-philanthropy, namely philanthropic activities through digital platforms both in the form of applications and social media, found its best momentum when the Covid-19 outbreak entered Indonesia and became a pandemic that had a huge impact on the Indonesian economy. The implementation of social distancing or physical distancing policies  causes economic activities to be hampered and causes a decrease in people's income. In an effort to synergize with the government to continued to maximized human development activities according to the Indonesian human development paradigm as a whole, namely Indonesian people who are physically healthy and fulfilled the needs of clothing, food and housing and have a healthy and strong mentality, the wider community as one of the stakeholders development can implemented its role. Through philanthropic activities. E-philanthropy through social media such as Facebook, Instagram, Twitter and WhatApp, as well as Digital Platforms or applications such as Kitabisa,Com, Amal Sholeh.Com, etc are quite important in this regard. Some of the identified forms of e-philanthropy included; (1) Family Philanthropy (18 institutions), (2) Corporate Philanthropy (17 institutions), (3) Religious Philanthropy (30 institutions), (4) Independent Philanthropy (37 institutions), and (5) Media Philanthropy (4 institutions) .As for the role of e-philanthropy in the development of human resources physically and as well as mentally/spiritually, it can be identified based on the e-philanthropy cluster formed based on the principle of the use of funds and their used. The philanthropic clusters are: (1) E-Philanthropy For The Zakat Cluster on Sustainable Development Goals (SDG's), (2) E-Philanthropy  Cluster For Indonesian Education, (3) Cluster E-Philanthropy For Residential Urban Areas, (4) E-Philanthropy  Cluster Philanthropy For Food   Nutrition Security, (5) Cluster E-Philanthropy For Health, (6) Cluster E-Philanthropy For Environment Conservation and also (7) Cluster E-Philanthropy For Arts Culture.Keyword : E-Filantrofi, Development, Socia Media, Platform Digital